Mapping of Community Pharmacy Practices in Medan City Indonesia - Ferendina, Imelda; W, Wiryanto; Harahap, Urip (Asian Journal of Pharmaceutical Research and Development, 2021)
Pharmaceutical practice standards are benchmarks used, especially pharmacists in carrying out pharmaceutical services. But this pharmaceutical practice has not been carried out by community pharmacy pharmacists. Pharmaceutical services are very dependent on the application of established practice standards. Therefore, revitalization efforts need to be made to meet the criteria of pharmaceutical practice in accordance with the applicable standards. This study aims to ensure that community pharmacy practice in Medan city and coaching efforts to restore pharmaceutical practices are in accordance with predetermined standards. This is a cross sectional descriptive research, using quistionnaires in Juni – September 2020. The research sample 105 pharmacist in community pharmacy taken by cluster random sampling. The results showed that the community pharmacy practice has not been running according to standards. The percentage of pharmacies with accreditation A was 67.6%, accredited B 21.0%, accredited C was 9.5%, and not accredited was 1.9%.While the percentage of very good category of pharmaceutical practice was only 20%, good category was 48%, just 21%, 9% less, and sub-standard criteria of 2%.Several factors play a role in determining the value of accreditation and pharmaceutical practice criteria after being statistically tested, namely the presence or absence of other jobs from pharmacists, pharmacy status, pharmacist's presence, and year of graduation from the pharmacist, with a significance <0.05.Based on the explanation can be concluded that the practice community pharmacy in the city of Medan has not met the established pharmaceutical standards.